A study on the mechanism of how sensory impairment affects depression in the elderly: the mediating roles of daily activity capability and social participation - Huang, Chunjie; He, Xiaoqing; Zhang, Xin (Frontiers in Psychology, 2024)
Objectives Through a longitudinal study, we explored the relationship between sensory impairments and depression in the elderly, and examined the mediating roles of daily activity capability and social participation within this relationship. Methods Based on data from the China Health and Retirement Longitudinal Study (CHARLS) collected in 2015 and 2018, a total of 4,419 individuals aged 60 and above were selected as research participants. Sensory impairments (predictor variables) were assessed in 2015 through self-rated visual and hearing capabilities. Daily activity capability and social participation (mediator variables) were also assessed in 2015, with daily activities assessed using the Basic Activities of Daily Living (BADL) and Instrumental Activities of Daily Living (IADL), and social participation assessed by the quantity of social activity participation. Depression status (outcome variable) was assessed in 2018 using the Center for Epidemiologic Studies Depression Scale (CESD-10). Statistical analysis was conducted using logistic regression and SPSS Macro PROCESS. Results First, there is a significant correlation between sensory impairments and an increased risk of depression among the elderly, including visual impairment (VI), hearing impairment (HI), and dual sensory impairment (DSI), all of which increase the likelihood of depression. Second, DSI indirectly affect depression through the cascading mediating effects of daily activity capability and social participation. Finally, in contrast to DSI, when there is only a single sensory impairment, either VI or HI, the cascading mediating effects of daily activity capability and social participation on depression are not statistically significant. Conclusion The elderly population with dual sensory impairments requires continued attention to help these individuals adopt preventive measures to halt the onset and worsening of depression.